Water Level Monitoring System Simulation Using Flutter Framework in Pekalongan City - Edifianto, Gilang Hendra Dita; Damarjati, Cahya; Asroni, Asroni (Emerging Information Science and Technology, 2021)
Pekalongan City is a region on the northern coast of Java with a sloping topography and is susceptible to the increasing sea level, which can result in tidal floods. As previous research revealed, ten villages in three districts, including coastal areas, are vulnerable to tidal floods. Moreover, the vulnerability analysis based on BNPB Head Regulation (Perka) No. 2 of 2012 unveiled that seven out of ten villages in three districts have a high risk of tidal floods. Pekalongan City experienced a tidal flood that swamped 16 villages in three districts at the beginning of 2021. It was the result of heavy rains and strong tides along the northern shore. The tidal flood caused damage to a variety of sectors, including agriculture, communities, infrastructure, and clean water sanitation. Information technology development was employed in disaster management, making it simpler to acquire data for predicting future disasters, obtaining data in disaster-affected areas, and implementing mitigation in disaster-prone areas. This study collected data through interviews and a literature review. This research created Android applications simulating a water level monitoring system using the flutter framework. Firebase was utilized as a database for authentication, while Google Maps Platform was deployed to display maps during the application simulation. It is anticipated that the simulation of the water level monitoring system will be the first step in building the water level monitoring system in Pekalongan City. Hence, residents of Pekalongan City can utilize it to assist with mobility issues during floods.